Portrait Of Poverty and Social Crime in The Short Story of Blora by Pramudya Ananta Toer - Rohmawati, Naili; Doyin, Mukh; Nugroho, Yusro Edy (Universitas Negeri Semarang, 2022)
The story of Blora by Pramudya Ananta Toer is a short story that describes the social reality of the people of Blora. The short story tells about the condition of the people of Blora during the colonial era who experienced poverty. Poverty is one of the factors in the condition of society that gives rise to social crimes. This study aims to reveal the facts of social problems that occur in the Blora community and find ways to overcome these social problems. This study uses a descriptive method with a sociological approach to the theory of Wellek and Warren. The data of this research are in the form of words, sentences, or dialogues that contain the facts of the story on the plot characters and the background about poverty and social crime in the short story entitled Stories from Blora by Pramudya Ananta Toer. The data collection technique was carried out by means of heuristic reading which included classifying, analyzing, and interpreting the data. The results showed that the descriptions of poverty and social crimes contained in the short stories appeared to occur in real terms in the Blora community. Both problems arise because of a causal relationship. Poor conditions in a society will lead to any crime to fulfill their needs. The benefit of the research is as an addition to knowledge to the reader regarding solving the problem of poverty and social crime in the Blora community.